2021
DOI: 10.1155/2021/9230866
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Pivotal Neuroimmunomodulation of Stem Cells in Spinal Cord Injury Repair

Abstract: Spinal cord injury (SCI) is a distressing incident with abrupt onset of the motor as well as sensory dysfunction, and most often, the injury occurs as result of high-energy or velocity accidents as well as contact sports and falls in the elderly. The key challenges associated with nerve repair are the lack of self-repair as well as neurotrophic factors and primary and secondary neuronal apoptosis, as well as factors that prevent the regeneration of axons locally. Neurons that survive the initial traumatic dama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 244 publications
(414 reference statements)
0
3
0
Order By: Relevance
“…After SCI, growth factors [e.g., vascular endothelial-derived growth factor (VEGF), glial cell-derived neurotrophic factor (GDNF), and brain-derived neurotrophic factor (BDNF), etc] were reported to have pro-repair impact on the microenvironment for supporting spontaneous neurofunctional recovery ( Richard and Sackey, 2021 ). Thus, we further evaluated the expression of multiple growth factors around the lesion core.…”
Section: Resultsmentioning
confidence: 99%
“…After SCI, growth factors [e.g., vascular endothelial-derived growth factor (VEGF), glial cell-derived neurotrophic factor (GDNF), and brain-derived neurotrophic factor (BDNF), etc] were reported to have pro-repair impact on the microenvironment for supporting spontaneous neurofunctional recovery ( Richard and Sackey, 2021 ). Thus, we further evaluated the expression of multiple growth factors around the lesion core.…”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al ( 110 ) found that ESWT enhanced the proliferation and differentiation of NSCs by Notch, PI3K/AKT, and Wnt/β-catenin Signaling, leading to the repairment of the damaged nerve function in central nervous system diseases. It is known that NSCs play a crucial role in the central and peripheral nervous system, and could replace damaged neural cells ( 111 114 ). It is clear that stem cell proliferation induced by ESWT is of great significance in the repair and regeneration of the nervous system.…”
Section: Cellular and Molecular Mechanismmentioning
confidence: 99%
“…Moreover, the presence of an electrical microenvironment favors the growth of neurons and myelination axon regeneration. Therefore, the design of injectable, conductive, ECM hydrogel materials may provide a new treatment modality for traumatic SCI [ 150 ]. For instance, Luo et al developed a native ECM biopolymer-based hydrogel containing polypyrrole that exhibited similar mechanical and conductive properties as native spinal cord tissue; the hydrogels enabled significant motor function recovery in the spinal cord of rats ( Fig.…”
Section: Hydrogel-based Novel Treatment Strategies For Scimentioning
confidence: 99%